Impact of Insulating Oil Degradation on the Power Transformer Frequency Response Analysis - Aljohani, O.; Abu-Siada, Ahmed; Islam, Syed (IEEE, 2015)
Frequency Response Analysis (FRA) has become a reliable tool to detect mechanical deformation within power transformers. Many researchers have investigated the impact of various mechanical winding and core deformations on transformer FRA signature using either simulation analysis or practical testing to establish a standard code for FRA signature interpretation. None of them however, have given attention to the impact of power transformer insulating oil degradation on the transformer FRA signature. This paper investigates the effect of insulating mineral oil degradation on power transformer FRA signature. In this regard, the physical geometrical dimension of a single-phase transformer filled with insulating mineral oil is simulated using three dimensional finite element analysis to emulate the real transformer operation. Transformer FRA signature is measured and analysed with various health conditions of the insulating oil. Results show that, insulating oil degradation has a significant impact on the transformer FRA signature.